Pemanfaatan Cendawan Mikoriza Arbuslcular (CMA) pada Beberapa Jenis Tanah terliadap Pertumbuhan Kacang Tanati {Arachis hipogaea L.) - SAMPURNO ' '; ELSIE ' '; OLFA RIANA ' (Jurnal Sagu, 2010)
In Indonesia, peanut {Arachis hipogaea L.) is an important legume type, occupying second positionafter soy. Utilization of CMA (Mycoriza Arbuskular) can increase peanut crop production, reduce agriculturalactivity cost and risk of pest trouble. This research was aimed to get best treatment of mycoriza for peanutgrowth. This research was conducted from May to August 2009 in farmer group of Jl. Gading Marpoyan,Simpang Tiga Village, Bukit Besar Regency Pekanbaru. This research used Randomized Group Design(RAK) by 12 treatments and 3 replications. Data is analyzed using anova and then continued with DNMRT of5% level. Result of research showed that treatment of 15 gram CMA at alluvial soil for peanut crop providedbest result for parameters of number of peas, number of flowers, dry seed weight and infection of mycoriza perplantKeywords: peanut, Mycoriza Arbuskular (CMA)